Short Communication: Correlation of Thermographic Ocular and Auricular Temperatures with Rectal Temperature in Anesthetized Dogs - Kapcak, Ayse Basak; Dogan, Elif (Wiley, 2023)
Objective. The aim of this study was to determine the correlation of both ocular and auricular thermographic temperatures with rectal temperatures and to determine the advantage of infrared thermography in clinical practice due to its ease of measurement. Animals. This study was designed as a pilot study and conducted on 6 mongrel male dogs during routine castration surgeries at the Kastamonu Municipality Temporary Animal Care Center. Methods. Rectal temperatures and ocular‐auricular thermographic images were taken from 6 dogs anesthetized (xylazine HCl 1 mg/kg and ketamine HCl 15 mg/kg) during routine neutering surgeries. Data were analyzed by Bland–Altman for correlation between rectal‐ocular and rectal‐auricular temperatures. Results. Rectal temperatures were significantly higher than orbital and auricular temperatures. In the correlation test, no significant difference and correlation were found between the measurements. Conclusion. As a result of the study, it was determined that the use of thermography was more advantageous than the waiting times of the digital thermometer used to record rectal temperatures. In addition, the noninvasive nature of thermography increased its acceptability in all dogs. The findings from this pilot study were considered to be at a level that could provide a basis for future studies.
Keywords: Veterinary medicine; SF600-1100; Research Article